2021
DOI: 10.1021/acschemneuro.0c00642
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Homogeneous and Heterogeneous Amyloid-β42 Oligomer Preparations with Biochemical Methods and Infrared Spectroscopy Reveals a Correlation between Infrared Spectrum and Oligomer Size

Abstract: Soluble oligomers of the amyloid-β(1-42) (Aβ42) peptide, widely considered to be among the relevant neurotoxic species involved in Alzheimer’s disease, were characterized with a combination of biochemical and biophysical methods. Homogeneous and stable Aβ42 oligomers were prepared by treating monomeric solutions of the peptide with detergents. The prepared oligomeric solutions were analyzed with blue native and sodium dodecyl sulfate polyacrylamide gel electrophoresis, as well as with infrared (IR) spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 84 publications
1
51
0
Order By: Relevance
“…This split band pattern is indicative of an anti-parallel β-sheet conformation (Barth, 2007;Cerf et al, 2009;Sarroukh et al, 2013). Earlier studies in our laboratory have shown a relationship between the position and width of this main band, and the size and homogeneity of the Aβ 42 oligomers (Vosough & Barth, 2021). The lower band position of the larger oligomers is in line with this relationship and our previous results, and confirms the different sizes of the oligomers produced at the two SDS concentrations.…”
Section: Ftir Spectroscopy: Effects Of LI + Ions On Aβ 42 Oligomer Structuresupporting
confidence: 91%
See 4 more Smart Citations
“…This split band pattern is indicative of an anti-parallel β-sheet conformation (Barth, 2007;Cerf et al, 2009;Sarroukh et al, 2013). Earlier studies in our laboratory have shown a relationship between the position and width of this main band, and the size and homogeneity of the Aβ 42 oligomers (Vosough & Barth, 2021). The lower band position of the larger oligomers is in line with this relationship and our previous results, and confirms the different sizes of the oligomers produced at the two SDS concentrations.…”
Section: Ftir Spectroscopy: Effects Of LI + Ions On Aβ 42 Oligomer Structuresupporting
confidence: 91%
“…The lower band position of the larger oligomers is in line with this relationship and our previous results, and confirms the different sizes of the oligomers produced at the two SDS concentrations. We have recently observed that a number of transition metal ions induce significant effects on the main band position for Aβ 42 oligomers (Vosough & Barth, 2021). Because the spectra for Aβ 42 oligomers formed with different amounts of LiCl generally superimpose on the IR spectra for the Li + -free oligomers, with no shifts observed for the main band, it appears that Li + ions have no significant effect on the oligomers' size or secondary structure.…”
Section: Ftir Spectroscopy: Effects Of LI + Ions On Aβ 42 Oligomer Structurementioning
confidence: 99%
See 3 more Smart Citations